PROSPEK LAHAN SAWAH LEBAK UNTUK PERTANIAN BERKELANJUTAN DI KABUPATEN BANYUASIN PROVINSI SUMATERA SELATAN - Syahputra, Fikri; Inan, Ishak Yuarsah (Indonesian Journal of Socio Economics, 2019)
The prospect of the resources of lebak lebak rice fields that are owned and strategic location with good accessibility, is a basic capital and a great opportunity for the development of the food crop agriculture sector on a regional and national scale.  Efforts to utilize lebak rice fields will still face a number of obstacles, so the application of specific technologies based on the conditions and characteristics of the land is very important.  This research aims to study the potential of lebak rice fields for the development of sustainable agriculture in Banyuasin Regency.  This research uses Participatory Rural Appraisal (PRA) analysis method.  Data analysis was performed descriptively quantitative.  Data collection uses observation techniques, group discussions, and interviews.  From the results of the discussion it is known that the pattern of planting and cultivation of lebak rice fields farming generally uses local varieties with a planting season period once a year.  Rice fields are the main source of livelihood for the people of Banyuasin Regency, which is estimated to be around 180-200 thousand families depending on the existence of rice fields.  On the other hand the low human resources related to the level of adoption of agricultural technology so that it becomes one of the obstacles in the development of lebak rice fields. Keyword : rice fields; sustainable agriculture